EPISTEMOLOGI ISLAM DALAM FILSAFAT MUHAMMAD TAQI MISHBAH YAZDI - Nurdin, Nurdin; AR, Muh. Sabri; Mustafa, Mustari (Program Pascasarjana, UIN Alauddin Makassar, 2016)
The article explored critically the Islamic epistemology thought of Muhammad Taqi Mishbah Yazdi. Muhammad Taqi Mishbah Yazdi was a religious leader and a contemporary philosopher as well who was able to present critical and creative philosophical ideas. He played an important role in creating conducive conditions to the continuation and development of Islamic philosophical discourse, and tried to harmonize between peripatetic philosophy of Ibn Sina, Suhrawardi illumination philosophy, and philosophy of Muta'alliyah Mulla Sadra Wisdom. He was also believed to be able to respond to the discourses of contemporary thought, including a number of modern to postmodern school of thought. Therefore, the philosophical views of Mishbah Yazdi Mohammad Taqi reflected a rationalist who was very brave to break the philosophical tradition of the previous philosophers whom he said had become a sort of postulate and sacred. According to Muhammad Taqi Mishbah Yazdi, knowledge was divided into two parts: First, tasawwur was gained through the particular and universal concepts of knowledge. This universal concept was used to define an object. It was also as a critique towards empiricism, and that this concept was not derived from sense perception. Through tasawwur, it was gained the primary concept i.e. māhiyah concept, and secondary concepts consisting of philosophical and logical secondary concepts. By the secondary concept, humans could come to the independent since it was not derived from nature but from reason and action analysis comparison. The concept of causality for instance. Second, the knowledge of taṣdῑq (affirmation) was assessing the concept, meaning that taṣdῑq was related to a proposition, according to Muhammad Taqi Mishbah Yazdi, the role and priority was reasonable in taṣdῑq, did not even need a sensory experience, for example: First, the analytical propositions that concept of the predicate was already included in the subject. Second, the badῑhῑ proposition did not require the sensory experience, although it required the senses in tasawwur or its conception. For instance: secondary badῑhῑ